Associations between child disciplinary practices and bullying behavior in adolescents - Graziela A.H. Zottis; Giovanni A. Salum; Luciano R. Isolan; Gisele G. Manfro; Elizeth Heldt (Elsevier, 2014)
Objective: to investigate associations between different types of child disciplinary practices and children and adolescents' bullying behavior in a Brazilian sample. Methods: cross-sectional study, with a school-based sample of 10- to 15-year-old children and adolescents. Child disciplinary practices were assessed using two main subtypes: power-assertive and punitive (psychological aggression, corporal punishment, deprivation of privileges, and penalty tasks) and inductive (explaining, rewarding, and monitoring). A modified version of the Olweus Bully Victim Questionnaire was used to measure the frequency of bullying. Results: 247 children and adolescents were evaluated and 98 (39.7%) were classified as bullies. Power-assertive and punitive discipline by either mother or father was associated with bullying perpetration by their children. Mothers who mostly used this type of discipline were 4.36 (95% CI: 1.87-10.16; p < 0.001) times more likely of having a bully child. Psychological aggression and mild forms of corporal punishment presented the highest odds ratios. Overall inductive discipline was not associated with bullying. Conclusions: bullying was associated to parents' assertive and punitive discipline. Finding different ways of disciplining children and adolescents might decrease bullying behavior. Resumo: Objetivo: investigar a associação entre práticas parentais de disciplina e comportamento de bullying entre adolescentes brasileiros. Métodos: estudo transversal, com alunos de 10 a 15 anos. Práticas parentais de disciplina foram avaliadas utilizando duas subclassificações principais: autoritárias e punitivas (agressão psicológica, punição corporal, retirada de privilégios e penalidades) e indutivas (explicações, recompensa e monitoramento). Uma versão modificada do Olweus Bully Victim Questionnaire foi utilizada para verificar a frequência de bullying. Resultados: foram avaliados 247 adolescentes, e 98 (39,7%) deles foram classificados como agressores. Práticas parentais de disciplina autoritárias e punitivas, utilizadas tanto pela mãe como pelo pai, apresentaram associação com a prática de bullying pelos filhos. Mães que mais utilizavam este tipo de disciplina apresentaram chance 4,36 (IC95%: 1,87-10,16; p < 0,001) vezes maior de ter um filho agressor. Agressão psicológica e formas brandas de punição corporal apresentaram os maiores odds ratio. Disciplina indutiva como um todo não apresentou associação. Conclusões: a prática de bullying apresentou associação com a disciplina parental autoritária e punitiva. A utilização de diferentes formas de disciplinar os adolescentes podem diminuir o comportamento de bullying. Keywords: Bullying, Adolescent, Punishment, Child rearing, Palavras-chave: Bullying, Adolescente, Punição, Educação infantil